2015
DOI: 10.1016/j.susc.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Ar implantation beneath graphene on Ru(0001): Nanotents and “can-opener” effect

Abstract: Exposing a monolayer of graphene on ruthenium (g/Ru(0001)) to low energy Ar + ions leads to nanotent formation and "can-opener" effect, similar phenomena as observed for h-BN/Rh(111) targets [1]. Nanotents are extra protrusions in the sp 2 monolayers beneath which atoms are immobilized at room temperature. Annealing the Ar + implanted structures results in the "can-opener" effect,i.e., the formation of the voids with a diameter about 2 nm within the graphene layer. The voids preferentially settle in the "hill"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In the past few years, ion-induced damage and annealing of Gr on a metal substrate has been intensely investigated: trapping of single noble gas ions under Gr on Ru(0001) [38]; formation of highly pressurized gas blisters under Gr on Pt(111) [39], Ir(111) [40][41][42], Ir(100) [43], and Ni(111) [44,45] upon annealing subsequent to noble gas implantation, damage evolution with ion energy [46]; formation of a regular arrangement of vacancy clusters with moiré periodicity (nanomesh) [47]; interface channeling [47]; and sputter protection of the substrate through a Gr cover [48]. In these studies, room-temperature irradiated Gr demonstrated a remarkable ability to self-repair upon annealing, which one might relate to the flexible bond reorganization in this material.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, ion-induced damage and annealing of Gr on a metal substrate has been intensely investigated: trapping of single noble gas ions under Gr on Ru(0001) [38]; formation of highly pressurized gas blisters under Gr on Pt(111) [39], Ir(111) [40][41][42], Ir(100) [43], and Ni(111) [44,45] upon annealing subsequent to noble gas implantation, damage evolution with ion energy [46]; formation of a regular arrangement of vacancy clusters with moiré periodicity (nanomesh) [47]; interface channeling [47]; and sputter protection of the substrate through a Gr cover [48]. In these studies, room-temperature irradiated Gr demonstrated a remarkable ability to self-repair upon annealing, which one might relate to the flexible bond reorganization in this material.…”
Section: Introductionmentioning
confidence: 99%
“…With similar low ion energies substitutional N implantation of Gr on SiC was accomplished by Telychko et al 19 . For low energies and fluences (negligible damage), Cun et al [20][21][22][23] demonstrated that implanted Ar + ions may come to rest under a 2D-layer strongly adhering to a metal surface and remain there upon annealing. In a recent comment 24 to a paper by Herbig et al 25 , we pointed out that Xe + irradiation of Gr on Ir(111) is accompanied by Xe trapping at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…For supported 2D systems, the evolution of defects, e.g., vacancies, may also be dominated by the interaction of defects with the substrate. [42][43][44]…”
Section: Response Of 2d Materials To Energetic Particle Irradiationmentioning
confidence: 99%